Isolation of Cellulose-Degrading Bacteria from Luwu Timur in Oil Palm Empty Fruits Bunch - Amalyah Febryanti; Maswati Baharuddin; Irma Rahayu (Walisongo Journal of Chemistry, 2021)
The oil palm empty fruit bunch (OPEFB) is one of the solid wastes produced by industrial factories. These bunches are the habitat of cellulolytic bacteria. This study aims to identify the morphology and determine the potential microorganisms in degrading oil palm empty fruit bunches waste. The methods used in this study were isolation and observation of bacterial morphology, bacterial screening, degradation test of empty oil palm fruit bunches waste, and enzyme activity test with DNS method using UV-Vis spectrophotometer at a wavelength of 530 nm. A collection of 14 isolates were obtained from the isolation process.  We obtained 14 isolates from the sample, the largest clear zone was shown by isolate S10.   The isolate also exhibited the highest cellulose-degrading activity after 7 days incubation period with a degrading percentage of 13.27%. After incubation for 2 days, the morphological characteristics of the bacteria produced have circular and medium-sized colonies, yellow, colonies wave edges and flat colonies, elevation convex and smooth surface. The resulting enzyme activity was 0.1308 U/mL. Therefore, isolate S10 was suspected to have the potential to degrade plastic.